Miscarriage of Meaning (Poem) - B. Nicholson (Law Text Culture, 2002)
1901 and the great Australian silence fell with deafening reality over the brown earth. A silence, screaming out its permanency in mortar and sand, recording in Joycean confusion, tho' lacking his learning and wit, that ineluctable modality he would ascribe to Bloom some years on. What measure of law could flaunt its own origins so glibly?